2019
DOI: 10.2174/1874210601913010085
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Breathing Pattern Changes, Sleep Quality, and Fatigue in Children after Rapid Maxillary Expansion: A Survey and Case Series Study

Abstract: Background: Rapid Maxillary Expansion (RME) aims to re-establish balance between the widths of the jaws. It is mainly utilized to treat skeletal and dental manifestations associated with transverse maxillary constriction and to improve facial structures involving the nasal cavity. Objectives: This study aimed to investigate parents’ perceptions of breathing pattern changes after their child had undergone RME and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Most studies (10/18) were conducted in Brazil ( 2 , 3 , 6 , 12 , 15 , 19 , 20 , 21 ), six in Italy ( 13 , 22 - 26 ) , one in Spain ( 14 ) and one in the USA ( 27 ). The studies dated from 2005 to 2019 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies (10/18) were conducted in Brazil ( 2 , 3 , 6 , 12 , 15 , 19 , 20 , 21 ), six in Italy ( 13 , 22 - 26 ) , one in Spain ( 14 ) and one in the USA ( 27 ). The studies dated from 2005 to 2019 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the effects of RME on naso-maxillary structures and nasal patency in MB as well as to verify the stability of these variables in the long term, the present review found that most studies (16/18) showed an increase in naso-maxillary structures (nasal cavity, oropharynx, nasopharynx, maxillary sinuses, maxillary width and dental arches) with RME ( 2 , 6 , 16 , 27 ). The effects on soft tissue structures of the nose were found on computed tomography scans three months after RME in the study by Badreddine et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation